Potential and Limitations of Atrial Natriuretic Peptide as Biomarker in Pediatric Heart Failure—A Comparative Review - Gangnus, Tanja; Burckhardt, Bjoern B. (Frontiers in Pediatrics, 2019)
Although B-type Natriuretic Peptide (BNP), N-terminal-proBNP (NT-proBNP) and mid-regional-proANP (MR-proANP) are included in current guidelines on heart failure in adults, no guideline considering these biomarkers in pediatric heart failure is available. A new drug class of neprilysin inhibitors as fixed-dose combination (Sacubitril/valsartan) has been introduced and is currently being investigated in children suffering from heart failure. Atrial Natriuretic Peptide (ANP) is discussed as a more useful alternative to BNP because it may grants better insights into the effects of this treatment. Thus, this review aims to provide an overview of the current knowledge concerning ANP in pediatric heart failure and compares its suitability regarding diagnosis and prognosis of heart failure. A literature search using PubMed resulted in 147 publications of which 22 studies were classified as relevant. The review presents available ANP, NT-proANP and MR-proANP level data in children (0-18 years). Summarizing, ANP shows only minor differences as marker for diagnosing and monitoring pediatric heart failure if compared to BNP. Due to its fast release, ANP offers the advantage of displaying rapid changes during therapy or operation. ANP is like the other natriuretic peptides influenced by age, presenting with the highest levels in very young infants. ANP also correlates with atrial pressure and volume overload in children. In addition, ANP determination in saliva appears to be a promising alternative to blood sampling. Similarly to NT-proBNP, NT-proANP and MR-proANP offer better stability but only few data has been published in children and thus their potential is only presumable so far.